Internal Communication Management: Increasing Employee Involvement And Motivation At PT Laz Coal Mandiri - Damayanti, Tarisa Alfira; Panuju, Redi; Abror, Dhimam; Harliantara, Harliantara; Maella, Nurannafi Farni Syam (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to know the role of internal communication management in increasing the participation and motivation of employees at PT Raz Call Mandiri. Using a qualitative approach, data was collected through in-depth employee interviews and internal document analysis. This study shows that effective internal communication management, including the use of digital technology and increased transparency, plays an important role in strengthening employee-management relations. The results of this study also highlight the importance of being sensitive to different organizational cultures in creating an inclusive and supportive working environment. Supportive leadership and communication practices that promote collaboration and innovation have also been identified as important factors in stimulating employee intrinsic motivation. Therefore, this study provides detailed information on how internal communication practices can be optimized to achieve higher engagement, increase motivation, and support the organization's sustainable goal achievement at PT Laz Coal Mandiri providing insight.